A CONCEPTUAL MALAYSIAN PRIVATE HEALTHCARE UNIVERSITY-OF-THE-FUTURE BUSINESS MODEL: STAYING RELEVANT IN THE DIGITAL AND POST-COVID ERA - Saiid, Muhammad (Journal of Information Systems and Digital Technologies, 2022)
In today's increasingly inter-connected and globalized world, global mega forces including geopolitical, economic, technological and environmental have caused the landscape of higher education to become volatile. Higher education institutes (HEIs) have been faced with increasing scrutiny, competition, regulation, financial and societal challenges. Moreover, along with the unexpected arrival of the COVID-19 pandemic and various disruptors driving for change including the evolution of digital technologies, democratization of knowledge, global mobility, demographic shifts, and the rise of online educational services, HEIs are in need of new alternate business models for agility, relevancy, and to continue to thrive and operate to offer value and reclaim their position as drivers of innovation, economic development and societal wellbeing. This paper develops and proposes through the adoption of the design thinking methodology an alternate conceptual business model for a Malaysian private healthcare University-of-the-Future (UotF) using the renowned Business Model Canvas (BMC) and Strategy Canvas (SC) frameworks. The results form the analysis and design of the BMC and SC indicates that the principal changes required to digitally transform the university to a UotF includes: the adoption of an open learning system for flexible and lifelong learning; transitioning the campus to a more 'smart', eco-friendly and sustainable campus; incorporating the latest artificial intelligence, machine learning algorithms, and data analytics to improve the university‘s management systems and enhance delivery mechanisms for teaching and learning; and to improve community engagement relationships and partnerships to deliver value to the economic, health and safety of the society, as well as to leverage the open learning system to provide curated courses to niche categories of students locally and globally.